How to Legalize Medically Assisted Death in a Free and Democratic Society - Browne, Alister (Cambridge quarterly of healthcare ethics, 2020)
In 2015, the Supreme Court of Canada struck down the criminal law prohibiting physician assisted death in Canada. In 2016, Parliament passed legislation to allow what it called ‘medical assistance in dying (MAID).’ The authors first describe the arguments the Court used to strike down the law, and then argue that MAID as legalized in Bill C-14 is based on principles that are incompatible with a free and democratic society, prohibits assistance in dying that should be permitted, and makes access to medically-assisted death unnecessarily difficult. They then propose a version of MAID legislation (‘Ideal MAID’) that gives proponents and opponents of MAID everything they can legitimately want, contend that it is the only way to legalize MAID that is compatible with a free and democratic society, and conclude that it is the way to legalize MAID in Canada and other similarly free and democratic societies.